Integrated management of wilt of cumin (Cuminum cyminum L.) - D M Nandoliya, K B Jadeja, (Journal of Spices and Aromatic Crops, 2008)
Four components of integrated management namely, soil solarization, crop rotation, chemicalsand biocontrol agents were tested under field condition at Junagadh (Gujarat) for themanagement of wilt of cumin (Cuminum cyminum) caused by Fusarium oxysporum f. sp.cumini. Growing of sorghum (Sorghum bicolor) or maize (Zea mays) during kharif seasondid not reduce wilt incidence during the following rabi season. Soil solarization with 25 μmLLDPE plastic cover for 15 days in summer proved most effective in reducing wilt incidenceto 26.27% as against 44.90% in non-solarization and increasing yield to 396 kg ha-1 as against286 kg ha-1 in non-solarized plots. Application of carbendazim granules @ 10 kg ha-1 onemonth after sowing or Trichoderma viride in organic carrier @ 62.5 kg ha-1 at sowing timewere also effective. Integrating soil solarization followed by growing of sorghum in kharifand application of either carbendazim granules @ 10 kg ha-1 one month after sowing orapplication of T. viride in organic carrier @ 62.5 kg ha-1 was effective for the management ofcumin wilt.